Análise do escoamento em um ciclone adaptado com bicos aspersores de água utilizando fluidodinâmica computacional (CFD) - Oliveira, Ricardo Arbach Fernandes de (Universidade Federal de São Carlos, 2019)
Cyclonic separators are widely used in industries for gas-solid separation process. Its low cost in building, operating and maintenance, as well as the ability to operate at high temperatures and pressures, makes it a good choice for gas treatment. In ethanol production industries, sugarcane bagasse is used in the energy cogeneration process. However, the combustion produces soot, a particle matter noxious that can not be emitted into the atmosphere. Thus, by passing through a gas treatment, the amount of particulate matter emitted by the industry can be reduced. The cyclone is often used as a gas pretreatment device, due to its low collection efficiency. Its collection efficiency can be improved by coupling other equipment of higher collecting efficiency to the cyclone body, such as electrostatic precipitators or, more commonly, water nozzles. With advances in the computational area, the use of computational fluid dynamics (CFD) to optimize dry cyclones, increasing collection efficiency and reducing pressure drop, has been a very usual technique, for being a reliable and cheap tool. However, its usage is very restricted in the study of wet cyclones, due to the difficulty of simulating interactions between Lagrangian phases. Thus, an approach was proposed in this study that aims to estimate the collection efficiency within a wet cyclone without the need to model the Lagrangean interactions. Through a hybrid model using CFD and the mechanistic model of kinematic coagulation, it was possible to quantitatively estimate the increase of the efficiency of the cyclone collection using water nozzles. The model uses the Eulerian-Lagrangian approach to simulate the gas-particle and gas-droplet interactions for the characterization of the flow inside the equipment, in order to apply the results obtained by CFD in the kinematic coagulation model. In general terms, the results obtained were effective in representing the phenomena, showing that the equipment is economically feasible, reducing the cut-size diameter by 54,66% and improving the overall collection efficiency of particles by 10,92% with a low increase of water consumption.
Keywords: Ciclone; Ciclone úmido; Coagulação cinemática; Fluidodinâmica computacional; Escoamento multifásico; Cyclone; Wet cyclone; Kinematic coagulation; Computational fluid dynamics; Multiphase flow.; ENGENHARIAS::ENGENHARIA QUIMICA::OPERACOES INDUSTRIAIS E EQUIPAMENTOS PARA ENGENHARIA QUIMICA; ENGENHARIAS::ENGENHARIA QUIMICA::PROCESSOS INDUSTRIAIS DE ENGENHARIA QUIMICA